Perancangan sistem informasi peminjaman ruangan pada PT. Multi Aneka Pangan Nusantara - Mukhtar Adinugroho; Teguh Herlambang; Firman Yudianto; Dike Bayu Magfira (UKInstitute, 2023)
PT. Multi Aneka Pangan Nusantara is one of the producers in Indonesia engaged in the chocolate processing industry and has presented a variety of premium quality products. The company office has many rooms that can be borrowed for meeting purposes. The company has an IT section whose job is to control all parts related to media and communications. PT. Multi Aneka Pangan Nusantara, whose center is in Surabaya, has a logistics unit whose one of its tasks is to manage meeting room loans and manage equipment at the PT. Multi Aneka Pangan Nusanatara. This web-based room loan application plan aims to make it easier for consumers to borrow rooms in a structured manner so that companies are able to create new innovations and can be used in the future. The design that will be carried out is the creation of a room lending application as access to meeting rooms and other activities where this application uses an online PHP and MySQL-based website that is more efficient and scheduled in detail. Room lending information system application at PT. Multi Aneka Pangan Nusantara has features that are suitable to answer existing problems, namely user data, room data, providing information on the number of borrowers, viewing and searching for user data, rooms and transactions. The existence of this information system can answer problems by providing loan management solutions that can be more quickly and efficiently.